Efficiency of judicial systems: Model definition and output estimation - R. Ippoliti; G. Tria (Journal of Applied Economics, 2020)
Focusing on the Italian judicial system as our case study, we use Data Envelopment Analysis to estimate technical efficiency scores and reference values for policy makers. In detail, this work presents a comparative analysis of different model definitions to identify the most appropriate one, emphasizing the key role of case matters in this production process. According to our results, the North of Italy emerges as more efficient than the other Italian macro areas, although the gap significantly decreases when case matters are considered in the output estimation. Concerning the collected reference values, which might be adopted by policy makers to reform the judicial system, we can observe significant differences able to affect the reorganization of courts. Taking the proposed case study into account, it seems that improvements in court performance could be achieved by reforming civil procedures, which are the technologies applied by judges in their production process.
Keywords: 330; civil justice; Institutional efficiency; model definition; output estimation